2014
DOI: 10.4172/2168-9296.1000135
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Starfish, Pentaceraster regulus from Thondi, East Coast of India

Abstract: Starfish Pentaceraster regulus was collected from Thondi coast, this species usually have 5 arms. An unusual, abnormal sea star, P. regulus was found with only 4 arms. Then it was length, weight arm's length were measured and tabulated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…Arm number abnormalities are relatively common in the family Oreasteridae. Other studies have reported similar conditions for the congener P. regulus, a common starfish from the Western Central Pacific (James, 1999;Shanker & Vijayanand, 2014), P. linckii, widely distributed in the Indian Ocean (James, 1999;Chelladurai et al, 2015;Chelladurai & Doss, 2016), and P. nodosus, from the Indo-Pacific region (Chim & Tan, 2012). Abnormal arm number have been attributed to several causes like injury, regeneration errors, malnutrition, congenital issues, or damages in the metamorphosis process (Moore, 1974;Hotchkiss, 1979;Watts, Scheibling, Marsh, & McClintock, 1983).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Arm number abnormalities are relatively common in the family Oreasteridae. Other studies have reported similar conditions for the congener P. regulus, a common starfish from the Western Central Pacific (James, 1999;Shanker & Vijayanand, 2014), P. linckii, widely distributed in the Indian Ocean (James, 1999;Chelladurai et al, 2015;Chelladurai & Doss, 2016), and P. nodosus, from the Indo-Pacific region (Chim & Tan, 2012). Abnormal arm number have been attributed to several causes like injury, regeneration errors, malnutrition, congenital issues, or damages in the metamorphosis process (Moore, 1974;Hotchkiss, 1979;Watts, Scheibling, Marsh, & McClintock, 1983).…”
Section: Discussionsupporting
confidence: 52%
“…columbiae Gray, 1840 (Fisher, 1945), Nardoa galatheae (Lütken, 1864) (James, 1999), Pentaceraster regulus (Müller & Troschel, 1842) (James, 1999;Shanker & Vijayanand, 2014), Pisaster ochraceus (Brandt, 1835) (Fisher, 1945), and Protoreaster linckii (Blainville, 1830) (James, 1999;Chelladurai, Balakrishnan, Jayanthi, Ajeesh-Kumar, & Mohanraj, 2015;Chelladurai & Doss, 2016). Other species where abnormal ray numbers have been recorded include Protoreaster nodosus (Linnaeus, 1758), a starfish widely distributed in the Indo-Pacific region (Chim & Tan, 2012) and Archaster angulatus Müller & Troschel, 1842 from the Indian Ocean and western Pacific (Keesing, 2017).…”
mentioning
confidence: 99%
“…The wound can be healed by a regeneration of the arms or by just covering the wound by the growth of a body wall (Hotchkiss, 1979). At the time of the regeneration of the arms, the sea star may regenerate two arms instead of one or it may just close the wound without growing an additional arm (Shanker & Vijayanand, 2014). They are considered as an indicator of fishing intensity and biomarkers for pollution because of their important role in ecology.…”
Section: Introductionmentioning
confidence: 99%